Impact of street parking on delays and the average speed of traffic flow - Hrytsun, Oleh; Lanets, Oleksii; Solodkyy, Serhiy (Видавництво Львівської політехніки, 2020)
The article is devoted to the problem of the impact of street parking on delays and the average speed of traffic flow. The sections with different ways of putting vehicles near the roadway in the central part of Lviv city with the most saturated flow were exposed to scientific scrutiny. For this purpose, the program software PTV Vissim is used. The causes of the impact of street parking on traffic flow speed and roadway capacity are analyzed. Simulation model was created, with the use of which the operation of the street section where parking is allowed and without parking, and also the impact of the parking duration on the average speed of traffic flow and its delays were investigated. It is clarified that the least values the average traffic delay has with the parking duration of 900 and 1800 sec, and the biggest values it has with the duration of 300 sec. It is determined that during the street parking design parallel to the sidewalk it is necessary to implement the restriction of the parking duration to increase the road network capacity and traffic flow speed.
Keywords: road network; traffic flow; traffic intensity; speed of movement; capacity; roadcapacity ratio; traffic simulation; field research; queue length; traffic delays